2011
DOI: 10.1186/cc10246
|View full text |Cite
|
Sign up to set email alerts
|

Goal-directed haemodynamic therapy during elective total hip arthroplasty under regional anaesthesia

Abstract: IntroductionTotal hip replacement is one of the most commonly performed major orthopaedic operations. Goal-directed therapy (GDT) using haemodynamic monitoring has previously demonstrated outcome benefits in high-risk surgical patients under general anaesthesia. GDT has never been formally assessed during regional anaesthesia.MethodsPatients undergoing total hip replacement while under regional anaesthesia were randomised to either the control group (CTRL) or the protocol group (GDT). Patients in the GDT group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
76
0
5

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 149 publications
(82 citation statements)
references
References 26 publications
1
76
0
5
Order By: Relevance
“…Cecconi et al showed improved outcomes in 40 patients receiving regional anesthesia for hip arthroplasty [33]. Kapoor et al showed a decrease in the duration of mechanical ventilation, ICU LOS, and hospital LOS in patients undergoing cardiac surgery [34].…”
Section: Does Gdft Improve Outcomes?mentioning
confidence: 99%
“…Cecconi et al showed improved outcomes in 40 patients receiving regional anesthesia for hip arthroplasty [33]. Kapoor et al showed a decrease in the duration of mechanical ventilation, ICU LOS, and hospital LOS in patients undergoing cardiac surgery [34].…”
Section: Does Gdft Improve Outcomes?mentioning
confidence: 99%
“…It has also been observed that crystalloid preloading alone may not be sufficient in elderly to compensate for the decrease in systemic vascular resistance (19) . In recent years, goal directed therapy (GDT), a combination of intravenous fluids and inotropes during surgeries in which spinal anaesthesia is used, has been suggested since this therapy may improve outcomes by decreasing the rate of minor postoperative complications (20) . Therefore one should aggressively apply some preemptive clinical strategies to lower the risks for these patients.…”
Section: Discussionmentioning
confidence: 99%
“…Bu komplikasyonların başında nörolojik hasar yer almaktadır. Ultrasonografik değerlendir-me yapıldıktan sonra veya ultrasonografi eşliğinde bloğun gerçekleştirilmesi uygulama güvenliğini arttırır (36)(37)(38)(39)(40)(41)(42)(43)(44). Postoperatif erken dönemde ortaya çıkan ağrıyı azaltmak için multimodal analjezi tekniğinin bir parçası olarak lokal infiltrasyon analjezisi önerilir.…”
Section: Artroplastide Anesteziunclassified